Prediction of thermomechanical behavior of acrylonitrile butadiene styrene using a newly developed nonlinear damage-reliability model - Abderrazak En-naji; N. Mouhib; H. Farid; M. El Ghorba (Fracture and Structural Integrity)
The aim of this work was to evaluate the influence of temperature on the mechanical behavior of an amorphous polymer, namely acrylonitrile butadiene styrene (ABS), based on a series of uniaxial tensile tests on smooth specimens at different temperatures. The results demonstrate that the behavior of the polymers is strongly dependent on the temperature. Its influence on the physical characteristics during the study of polymer behaviors cannot be denied, particularly when the processes of shaping are investigated, which require significant contributions of heat and mechanical effort. For this reason, this study consists of predicting the evolution of ABS damage in two main zones. The first is the industrial zone, in which the configuration of macromolecular chains is largely immobile, and the temperature is below the glass temperature (Tg = 110°C). In this zone, a damage model based on the obtained experimental results allowed us to determine three stages of damage evolution, and then to specify the critical fraction of life, at which the material becomes unstable and defective, for the purpose of predictive maintenance. The second zone is that of thermoforming, in which the temperature is above the glass temperature, Tg. In this zone, the macromolecular chains tend to move more freely as the temperature increases. The same damage model was adopted to follow the flow process according to the fraction of life that represents the critical material parameter. This study also includes a comparison between the static (experimental) damage models and unified theory (theoretical) damage models.